2008
DOI: 10.1598/rrq.43.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Effective Reading Programs for Middle and High Schools: A Best‐Evidence Synthesis

Abstract: This article systematically reviews research on the achievement outcomes of four types of approaches to improving the reading of middle and high school students: (1) reading curricula, (2) mixed‐method models (methods that combine large‐and small‐group instruction with computer activities), (3) computer‐assisted instruction, and (4) instructional‐process programs (methods that focus on providing teachers with extensive professional development to implement specific instructional methods). Criteria for inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
168
1
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 21 publications
9
168
1
9
Order By: Relevance
“…Yet, at present there are few programs with strong evidence of effectiveness. In a recent systematic review of the research on middle-and high-school reading programs, Slavin, Cheung, Groff, and Lake (2008) found only 33 studies that met minimal requirements for inclusion in the review (e.g., experimental-control comparisons, controls for pre-test differences, duration of at least 12 weeks). Of the programs reviewed in these studies, none met the standards for 'strong evidence of effectiveness', but four programs met the standards for 'moderate evidence of effectiveness'.…”
mentioning
confidence: 99%
“…Yet, at present there are few programs with strong evidence of effectiveness. In a recent systematic review of the research on middle-and high-school reading programs, Slavin, Cheung, Groff, and Lake (2008) found only 33 studies that met minimal requirements for inclusion in the review (e.g., experimental-control comparisons, controls for pre-test differences, duration of at least 12 weeks). Of the programs reviewed in these studies, none met the standards for 'strong evidence of effectiveness', but four programs met the standards for 'moderate evidence of effectiveness'.…”
mentioning
confidence: 99%
“…The average impact estimate was 0.132 of a standard deviation, though the estimates ranged widely, from a low of 0.045 to a high of 0.762 of a standard deviation. In a more recent systematic review of computer-assisted instruction effects on reading, Slavin et al (2008) found a weighted mean effect of 0.1 of a standard deviation across eight eligible studies. Importantly, all of these studies focused on computerassisted instructional packages as standalone, supplemental interventions rather than as components of integrated, blended curricula.…”
Section: Computer-assisted Instruction Research Contextmentioning
confidence: 99%
“…The prescribed dosage is typically 90 minutes per day, five days per week (Loadman et al, 2011;Scholastic, n.d.). It is part of a class of interventions that Slavin et al (2008) refer to as "mixed-methods models" and what others call "blended learning" models (Horn and Staker, 2011), but, given that it prominently features an adaptive, computer-based component, we classify it as a computer-assisted approach in our analysis. Based on seven studies that meet evidence standards with reservations (comparable to a level 4 on the Maryland Scale), the WWC found potentially positive effects for the impact of Read 180 relative to comparison curricula on comprehension, with an average increase of 0.11 of a standard deviation, or 4 percentile points, and on general literacy achievement, with an average increase of 0.31 of a standard deviation, or 12 percentile points.…”
Section: Computer-assisted Instruction Research Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Best-evidence analyses rely on a small number of high-quality studies that meet specific selection criteria. Researchers may argue over the nature of the criteria, their application to particular studies, or the sufficiency of the evidence to support claims of effectiveness (Slavin, 1986(Slavin, , 2008Slavin, Cheung, Groff, & Lake, 2008).…”
mentioning
confidence: 99%